2019
DOI: 10.1177/1545968319834900
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Noninvasive Brain Stimulation on Poststroke Cognitive Function: A Systematic Review

Abstract: Supplementary material for this article is available on the Neurorehabilitation & Neural Repair website along with the online version of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 84 publications
1
15
0
Order By: Relevance
“…Among the excluded articles, 2 had less than 5 sessions or 5 days of NIBS [ 28 , 29 ]. Not only did this not adhere to the recommended schedule for treatment of depression, which has been highly evidenced in recent years, but it is also suggested that long-term cognitive improvement is likely related to the number of stimulation session/days, with more stimulation sessions resulting in a longer-lasting response [ 30 ]. In addition, one study evaluated a functional independence measure with the stimulation site being the primary motor cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Among the excluded articles, 2 had less than 5 sessions or 5 days of NIBS [ 28 , 29 ]. Not only did this not adhere to the recommended schedule for treatment of depression, which has been highly evidenced in recent years, but it is also suggested that long-term cognitive improvement is likely related to the number of stimulation session/days, with more stimulation sessions resulting in a longer-lasting response [ 30 ]. In addition, one study evaluated a functional independence measure with the stimulation site being the primary motor cortex.…”
Section: Resultsmentioning
confidence: 99%
“…The reason why we increased the total number of stimuli to 2,000 was to consider the possibility that increasing the number of stimuli might increase the efficacy and duration of rTMS treatments. A systematic review also concluded that long-term cognitive improvements are likely related to the number of stimulation sessions/days, where more stimulation sessions result in longer-lasting stimulation effects (van Lieshout et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since the current study is a conceptually novel approach, we estimated the necessary sample size based on the results of previous neglect studies that combined neglect treatment with NIBS that aimed at such ‘re-balancing’ in repeated sessions. The review of Van Lieshout and colleagues [ 52 ] reports four such RCT’s for which effect sizes are known or could be calculated. Cohen’s d ranged from 1.07-5.27 in two rTMS studies [ 53 , 54 ], 1.48-7.14 in two TBS studies [ 54 , 55 ], and 1.50-2.35 in one tDCS study [ 56 ].…”
Section: Methodsmentioning
confidence: 99%